Development of Nanofibers with Embedded Liposomes Containing an Immunomodulatory Drug Using Green Electrospinning - Luca Casula; Anže Zidar; Julijana Kristl; Matjaž Jeras; Slavko Kralj; Anna Maria Fadda; Špela Zupančič (MDPI AG, 2023)
Conventional treatments for chronic wounds are often ineffective, thus new therapeutic approaches are needed, such as the delivery of immunomodulatory drugs that can reduce inflammation, restore immune cell function, and facilitate tissue regeneration. A potential drug for such an approach is simvastatin, which has major drawbacks including poor solubility and chemical instability. With the aim of developing a dressing for wound healing, simvastatin and an antioxidant were incorporated into alginate/poly(ethylene oxide) nanofibers by green electrospinning without the use of organic solvents, thanks to their prior encapsulation into liposomes. The composite liposome-nanofiber formulations exhibited fibrillar morphology (160-312 nm) and unprecedentedly high phospholipid and drug content (76%). Transmission electron microscopy revealed dried liposomes as bright ellipsoidal spots homogeneously distributed over the nanofibers. After nanofiber hydration, the liposomes reconstituted in two size populations (~140 and ~435 nm), as revealed by cutting-edge MADLS® analysis. Lastly, in vitro assays demonstrated that composite liposome-nanofiber formulations are superior to liposomal formulations due to a better safety profile in keratinocytes and peripheral blood mononuclear cells. Furthermore, both formulations exhibited similarly advantageous immunomodulatory effects, measured as decreased inflammation in vitro. A synergistic combination of the two nanodelivery systems shows promise for the development of efficient dressings for chronic wound treatment.